Characterization of Nitrate Reductases from Corn Leaves (Zea mays cv W64AxW182E) and Chlorella vulgaris: Sensitivity to a Proteinase Extracted from Corn Roots - Poulle, M. (1987)
The sensitivity of the two forms of nitrate reductase, NR(I) and NR(II), obtained from the primary leaf of corn, to a limited action corn root proteinase has been examined. The corn inactivating protein (CIP) inhibited the overall reaction (NADH-NR) and the two partial reactions, cytochrome c reductase and reduced methyl viologen NR (MV-NR) of both forms of NR. NADH-cytochrome c reductase was more sensitive to the protease than MV-NR. NR(II) was less sensitive to inactivation than NR(I). When NR(I) and NR(II) were inactivated and then subjected to native gel electrophoresis the protein bands associated with MV-NR activity shifted from an R(m) value of 0.32 to 0.61 for NR(I) and from an R(m) of 0.28 to 0.60 for NR(II). For Chlorella NR these values are 0.32 and 0.70. The initial cleavage of the 116 kilodalton subunit of NR(I) yielded fragments of 84 and 80 kilodaltons after a 5 minute incubation with CIP. With longer incubation times smaller fragments were also identified. For the Chlorella NR the initial cleavage products are approximately 68 and 25 kilodaltons. Longer incubation times also led to smaller fragments. The products of hydrolysis by this limited action protease are quite different for the corn and Chlorella NRs.